Inter-plant competition for resources in maize crops grown under contrasting nitrogen supply and density: Variability in plant and ear growth - Rossini, Maria de Los Angeles (2011)
Increased plant population density in irrigated and fertilized maize crops enhances plant-to-plant variability since early vegetative stages, because the most suppressed individuals of the stand intercept less radiation per unit leaf area than the dominant ones (i.e. a size-asymmetric competition for light). Contrarily, a size-symmetric competition has been proposed for the acquisition of soil resources in a plant community (e.g. N capture per unit root length is similar among plants of different size). Hence, N fertilization effect on the variability of maize plants would depend on the initial plant-to-plant variability or on that promoted by a high plant population density. Two maize hybrids with contrasting tolerance to crowding (tolerant AX820 and intolerant AX877) were cultivated under different combinations of stand densities (6, 9 and 12plantsm-2) and N supplies (0 and 200kgNha-1) without water restrictions. Variability in plant growth rate among plants was computed along the cycle, especially after fertilizer was applied (i.e. the early reproductive period; PGRER) and during the critical period around silking (PGRCP). Plant-to-plant variability in biomass partitioning to the ear (partition index; PI), ear growth rate during the critical period (EGRCP) and kernel number per plant (KNP) was also established. Reduced N supply increased the coefficient of variation (CV) of PGRER, PGRCP, EGRCP and KNP (0.05